The journey from e-government to digital transformation: the case of Saudi Arabia. (4th November 2022) - Zygiaris, Sotirios; Maamari, Bassem E.
The e-government implementation process in the world is at various stages with some countries having a pronounced success. The governments with a greater degree of success are subject to the second stage of evolution known as digital government. In the digital government stage, organisations carry on internal service improvement in an attempt to change cultural impulses. The purpose of this study is to analyse the transition process from e-government to digital government in Saudi Arabia. We aim to identify the factors that would enable this transition. The findings of our study illustrate that in the journey from e-government to digital government there are four important enabling factors, namely technology adequacy, organisational change, open government and social inclusive government. The study provides a researcher's view of the factors that will lead a digital transformation process in government to incorporate internal socio-technical physiognomies that will promote a responsive, proactive, open and social government.